(untitled) (Educational Knowledge, 2023)
Reflective practice has become paramount in teacher training programs worldwide. This study examines the use of blogs to document reflective experiences of 28 student teachers during a ten-week period in 2018. The research aims to identify themes related to professional development, level of engagement with reflection, and perceptions of the advantages and disadvantages of utilizing blogs. Employing a constructivist epistemological framework and deductive content analysis, the study derives insights from blog entries and semi-structured interviews. Findings encompass professional development themes such as professional identity, self-efficacy, self-assessment, and self-regulation. While blogs facilitate collaborative learning and experience-sharing, challenges include privacy concerns, time constraints, effort, and variable engagement. Recommendations for pedagogical practice and future research are presented.